PREVENTION PROGRAM FOR PEOPLE LIVING WITH TYPE 2 DIABETES MELLITUS : A SYSTEMATIC REVIEW - Akub Selvia; Wahyu Gito Putro; Zaki Maulana Riski; Ninda Roudlotul Janah; Annisa Sabilia Andini; Agus Dwi Pranata (Poltekkes Kemenkes Aceh, 2023)
Noncommunicable diseases (NCDs) are diseases caused by a mix of genetic, physiological, environmental, and behavioral factors. The prevalence of NCDs is comparable to that of Diabetes Mellitus (DM) and hypertension. Diabetes Mellitus cases were 476 million worldwide in 2019, with 578 million anticipated in 2030 and 700 million predicted in 2045. This is a Systematic Review study that employs the